STUDI DESKRIPTIF KUALITATIF PROGRAM CSR PEMBERIAN BEASISWA KEPADA SISWA SMP MASYARAKAT BERPENGHASILAN RENDAH PDAM SURYA SEMBADA KOTA SURABAYA - Farikha Rachmawati; Ahimsa Adi Wibowo; Galih Ayu Palupi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
CSR is interpreted as a form of moral responsibility that needs to be given by companies to support the welfare and safety of the environment and society. PDAM Surya Sembada is one of the BUMDs that also participates in CSR activities. From several CSR activities in it, this research focuses on how the implementation process is, what are the weaknesses and strengths of the program and what impact is felt by the company in the MBR Middle School Student Scholarship Program. Through a qualitative method with a descriptive approach and data collection techniques in the form of in-depth interviews and documentation, the research shows that the CSR program of PDAM Surya Sembada is a form of strategic collaboration with the City Government and the Surabaya City Education Office and the implications of the obligation of CSR theory. Some strengths, weaknesses and impacts of program implementation were also found.